Fashion & Music (Springer Series in Fashion Business,, 2018)
This book will broaden readers' understanding of the links between the music and fashion industries. It highlights the challenges currently facing the fashion industry in terms of hyper-competition, definition of ever-faster trends, changing consumer demands etc. In fact, the fashion industry is heavily influenced by the digital revolution in the music industry, which has changed the face of individual music consumption and social reference, and therefore, also has impacts on fashion consumption and social reference. This understanding is crucial in order to realign any fashion company's strategies to the demands of modern fashion consumers. In terms of content, the book first discusses the social perspective of fashion and music. This includes an analysis of music as a key influencer of fashion trends, both theoretically and on the basis of a case study on grunge music. Then the role of music in the fashion business is addressed, and covers in-store music and the role o f music in fashion communication. Following up, the role of fashion in the music business is analyzed. This includes the trend of co-design of fashion collections, music artists' role of differentiation by style, and the market for music fashion merchandise articles (both theoretically and drawing on a case study). In closing, potential lessons learned from the music industry are developed for the fashion industry. This includes an analysis of the digital revolution and the advent of the crowdfunding idea (both theoretically and in a case study).